Developing a Contextual-Based Teaching Materials Planning Course at UIN Sumatera Utara, Medan - Zunidar, Zunidar (Didaktika Religia, 2022)
In light of the necessity for instructional materials that are tailored to the specific learning requirements of students, this study seeks to assess the viability of creating such materials for a course on planning and to evaluate their efficacy. The research method employed was that of development research. The teaching materials were validated by experts, following which individual tests, small group tests and field groups were conducted. The effectiveness of the learning model was evaluated using a t-test. The findings indicated that the teaching materials for the contextual-based learning planning course demonstrated a high level of feasibility for use in learning activities and were found to be effective for use in learning. Based on the statistical testing results (5.34) > t table (1.99), it can be concluded that the teaching materials developed are effective in improving student learning outcomes.